PENGARUH STATUS SOSIAL EKONOMI ORANGTUA TERHADAP PERILAKU ANAK (Studi di SMA Negeri 4 Bandar Lampung) - Fadila, Ade Citra; Hidayati, Dewi Ayu (SOCIOLOGIE, 2013)
This research was conducted in order to obtain an objective picture of the behavior of students who responded to the child and to determine the effect of parental socioeconomic status on childrens behavior in SMA Negeri 4 Bandar Lampung. The population in this study were all students aged between 15 to 18 years, drawn at random from the class X, XI, and XII while as many as 108 samples determined through Qaisquare techniques. Data were collected through questionnaires and documentation that support the research. After going through the stages of processing, the data were analyzed with quantitative approaches aimed at explanation by using a single table, while the test was used to test statistical hypothesis Qaisquare. The results showed that there was the influence of parental socioeconomic status(including education level, occupation, and income level parental) on childrens behavior with the result of 1.01, 1.05, 0.9. The effect is the tendency of the higher socio-economic status of the parents then the childs behavior is not likely either. From the calculation of the correlation between parental socioeconomic status on childrens behavior count r value of 1.00 compared to the tables at 1% significance level. R count rates of 1,00 shows the influence of parental socioeconomic status on childrens behavior is relatively high.Â Keywords: Socioeconomic status parents, child behavior